A Rare Case of Intraconal Orbital Schwannoma - Savithri Ravindra; Raghuraj Hegde; B. Meghana (Archives of Medicine and Health Sciences)
Schwannoma is a benign, slow-growing peripheral nerve sheath tumor that originates from Schwann cells. Orbital schwannoma is relatively rare, accounting for only 1% of all orbital neoplasms. Intraconal orbital schwannoma (within the muscle cone) is rarer still. We present a case of 68-year-old male with painless, slow-growing mass with protrusion of the right eye. The mass was excised after lateral orbitotomy and tissue diagnosis was made on histopathological examination.